K-alpha and bremsstrahlung x-ray radiation backlighter sources from short pulse laser driven silver targets as a function of laser pre-pulse energy - Jarrott, L; Kemp, A; Divol, L; Mariscal, D; Westover, B; McGuffey, C; Beg, F; Suggit, M; Chen, C; Hey, D; Maddox, B; Hawreliak, J; et al. (2014)
Measurements of silver K-shell and bremsstrahlung emission from thin-foil laser targets as a function of laser prepulse energy are presented. The silver targets were chosen as a potential 22 keV backlighter source for the National Ignition Facility Experiments. The targets were irradiated by the Titan laser with an intensity of 8 × 1017 W/cm2 with 40 ps pulse length. A secondary nanosecond timescale laser pulse with controlled, variable energy was used to emulate the laser prepulse. Results show a decrease in both Kα and bremsstrahlung yield with increasing artificial prepulse. Radiation hydrodynamic modeling of the prepulse interaction determined that the preplasma and intact target fraction were different in the three prepulse energies investigated. Interaction of the short pulse laser with the resulting preplasma and target was then modeled using a particle-in-cell code PSC which explained the experimental results. The relevance of this work to future Advanced Radiographic Capability laser x-ray backlighter sources is discussed. © 2014 AIP Publishing LLC.